QUALITY ASSURANCE IN HIGHER EDUCATION IN THE CONTEXT OF TRAINING EDUCATIONAL MANAGERS: THE UNITED KINGDOM EXPERIENCE - Ткаченко, В. П. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The article examines the main features of training the heads of educational establishments in the United Kingdom. The overview of universities, which are engaged in such training, was carried out. Determined the legal documents that governing the activities of mentioned programs in the context of the quality assurance in each region (England, Scotland, Northern Ireland and Wales). According to the regional distribution was carried out the informational overview of the standards that define the basic principles of training educational managers, the basic elements of such documents and characteristics that facilitate the implementation of standards through a combination of competencies, skills and personal abilities of manager and quality assurance at providing educational services